Study of partition of nitrazepam in bile salt micelles and the role of lecithin - de Castro, Baltazar (2019)
The effect of trihydroxy (sodium cholate and sodium glycocholate) and dihydroxy (sodium deoxycholate and sodium glycodeoxycholate) bile salt micelles on the spectrophotometric properties and on the solubility of nitrazepam in aqueous solution, at 25.0°C and at ionic strength 0.1 M in sodium chloride, has been assessed. From the results obtained it was possible to calculate the partition coefficients (Kp) of nitrazepam between aqueous and micellar phases. The partition coefficients of nitrazepam have also been determined in mixed micelles of cholate or deoxycholate with lecithin (egg yolk phosphatidylcholine), which were used as a model of the gastrointestinal tract. Drug partition was found to depend on the bile acid (number of hydroxyl groups and conjugation with glycine), and our data indicate further that addition of lecithin to bile salt micelles decreases the values of the partition coefficients in the mixed micelles at physiological pH.